Civic Learning: A Sine Qua Non of Service Learning - Bringle, Robert G.; Clayton, Patti H. (Frontiers in Education, 2021)
Civic learning is an essential element of service learning, but one that is often underdeveloped in practice. This article surveys various conceptualizations of civic learning, discusses approaches to designing service learning courses to generate civic learning outcomes, and proposes some methods for assessing student attainment of them. The intent is to build instructors' capacities to cultivate the knowledge, skills, and dispositions that lie at the very heart of civic learning and of public life in the ever-more complex and interconnected 21st century.